Identification of avian polyomavirus and its pathogenicity to SPF chickens - Zhai, Tianshu; Yan, Jiajia; Wang, Jia; Kong, Dongni; Hou, Lidan; Deng, Yong; Gu, Guoqian; Wang, Tuanjie; Wang, Xi; Xue, Qinghong; Yin, Chunsheng; Cheng, Jia; et al. (Frontiers in Microbiology, 2024)
The research aimed to study an APV strain that was isolated in Shandong, China. To study the pathogenicity of avian polyomavirus (APV) in SPF chickens, and provide references for epidemiological research and disease prevention and control of APV. The genetic characterization of APV strain (termed APV-20) was analyzed and the pathogenicity of APV was investigated from two aspects: different age SPF chickens, and different infection doses. The results revealed that the APV 20 exhibits a nucleotide homology of 99% with the other three APV strains, and the evolution of APV In China was slow. In addition, the APV-20 infection in chickens caused depression, drowsiness, clustering, and fluffy feathers, but no deaths occurred in the infected chickens. The main manifestations of necropsy, and HE staining showed that one-day-old SPF chickens were the most susceptible, and there was a positive correlation between viral load and infection dose in the same tissue. This study showed that SPF chickens were susceptible to APV, and an experimental animal model was established. This study can provide a reference for the pathogenic mechanism of immune prevention and control of APV.